2022
DOI: 10.1001/jamacardio.2022.0810
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among Patients With Early-Onset Atrial Fibrillation and Rare Variants in Cardiomyopathy and Arrhythmia Genes

Abstract: IMPORTANCE Patients with early-onset atrial fibrillation (AF) are enriched for rare variants in cardiomyopathy and arrhythmia genes. The clinical significance of these rare variants in patients with early-onset AF is unknown.OBJECTIVE To assess the association between rare variants in cardiomyopathy and arrhythmia genes detected in patients with early-onset AF and time to death. DESIGN, SETTING, AND PARTICIPANTSThis prospective cohort study included participants with AF diagnosed before 66 years of age who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…To date, a majority of the evidence for risk associated with P/LP variants is based on samples largely comprising individuals of European ancestry. Indeed, the UK Biobank and the Vanderbilt AF registry in the Yoneda study 8,9 are mainly inclusive of participants who self-reported White race in contrast with the Patel study that now extends similar conclusions to participants of African ancestry from the ARIC cohort. 10 A prior genotype-first, electronic health records study using the Geisinger and University of Pennsylvania biobanks demonstrated that TTNtv were associated with diagnostic codes for AF, HF, ventricular arrhythmias, and sudden death.…”
Section: Related Articles Pages 723 and 733mentioning
confidence: 82%
See 1 more Smart Citation
“…To date, a majority of the evidence for risk associated with P/LP variants is based on samples largely comprising individuals of European ancestry. Indeed, the UK Biobank and the Vanderbilt AF registry in the Yoneda study 8,9 are mainly inclusive of participants who self-reported White race in contrast with the Patel study that now extends similar conclusions to participants of African ancestry from the ARIC cohort. 10 A prior genotype-first, electronic health records study using the Geisinger and University of Pennsylvania biobanks demonstrated that TTNtv were associated with diagnostic codes for AF, HF, ventricular arrhythmias, and sudden death.…”
Section: Related Articles Pages 723 and 733mentioning
confidence: 82%
“…In this issue of JAMA Cardiology, Yoneda et al 9 now report the clinical outcomes in EOAF, comparing P/LP gene carriers with noncarriers and demonstrating that these P/LP variants are associated with poorer outcomes. Over 10 years of follow-up, 219 individuals or 17% of the overall EOAF cohort (n = 1293) died.…”
Section: Related Articles Pages 723 and 733mentioning
confidence: 99%
“…Therefore, our data suggest that in these types of patients, a detailed examination of the heart’s morphology and function (using CMR imaging), as well as regular follow-ups are required, especially in TTNtv-related AF cases. Yoneda et al recently showed that the presence of disease-causing variants in cardiomyopathy- and arrhythmia-associated genes are related to a higher mortality risk in patients with early-onset AF, thus revealing this disease entity to be less benign than previously thought [ 41 ]. However, data on the impact of structural gene variants on AF burden, quality of life and risk of stroke is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…The death risks were significantly higher in younger dementia patients with AF than older dementia patients with AF could be due to several reasons ( 3 , 5 , 39 ): First, a diagnosis of young onset dementia has a unique impact, differing from that experienced by older individuals. Besides, prior research indicated that uncommon genetic variations-related arrhythmia may increase the likelihood of mortality in patients suffering from early-onset AF, particularly in those diagnosed at a young age ( 40 ). For individuals who are diagnosed with both young-onset dementia and AF, the condition tends to be more severe and progress rapidly, contributing to a higher mortality rate ( 37 ).…”
Section: Discussionmentioning
confidence: 99%